Commitment in the Artistic Practice of Aref El-Rayess : the Changing of Horses - Gasparian, Natasha (Anthem modern and contemporary art of the Arab world, Iran and Turkey, 2020)
In her study of Aref El-Rayess's The 5th of June, or, The Changing of Horses, Natasha Gasparian reveals that the picture was presented and received, allegorically or metaphysically, as an idealized narrative of national liberation. By tracing the caesuras and slips in discourse, she reconstructs an alternative reading of the artwork's uncanny yet historically determinate character.